2011
DOI: 10.1097/00004872-201106001-00011
|View full text |Cite
|
Sign up to set email alerts
|

Summer Does Not Always Mean Lower: Seasonality of 24 H, Daytime and Night-Time Blood Pressure

Abstract: Evaluation of seasonal influences on ambulatory blood pressure monitoring (ABPM) values in a very large population living in a mild-climate geographic area.Methods: Among patients referred to our Hypertension Center between September 2002 and January 2011 with a reliable ABPM, we considered those in the two hottest (July and August) vs. those in the two coldest (January and February) months.Results: Seven hundred and forty-two men (53.2%) and 653 women (46.8%) were studied; 1245 (89.3%) were hypertensive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 13 publications
5
28
0
3
Order By: Relevance
“…BP phenotypes are probably more closely related to the mediumto-long-term variation in atmospheric conditions rather than to the short-term variation, as exemplified by our current 24-hour ambulatory monitoring enabled us to study the BP rhythmicity during the whole day. [9][10][11][16][17][18][19][20] Our methods were concordant with a recent study 11 that also applied multivariable regression analyses to investigate the independent effects of host and environmental factors, including personal-level temperature, relative humidity, atmospheric pressure, and daylight hours (seasonality). However, the outcome variables in this study were 24-hour daytime and nighttime BPs instead of the night-to-day BP ratio.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…BP phenotypes are probably more closely related to the mediumto-long-term variation in atmospheric conditions rather than to the short-term variation, as exemplified by our current 24-hour ambulatory monitoring enabled us to study the BP rhythmicity during the whole day. [9][10][11][16][17][18][19][20] Our methods were concordant with a recent study 11 that also applied multivariable regression analyses to investigate the independent effects of host and environmental factors, including personal-level temperature, relative humidity, atmospheric pressure, and daylight hours (seasonality). However, the outcome variables in this study were 24-hour daytime and nighttime BPs instead of the night-to-day BP ratio.…”
Section: Discussionsupporting
confidence: 67%
“…Seasonal BP variation has often been attributed to the changes in outdoor temperature. 20 However, most studies searched for the influence of season 10,31 or temperature alone 16 or both without mutual adjustment. 9,12,14,17,18 Only few studies investigated the influence of season on BP adjusted for temperature 11,13 or conversely adjusted the influence of temperature for season.…”
mentioning
confidence: 99%
“…Although carried out on biased groups (members of different summer and winter populations that had been selected to attend hypertension clinics), ABP studies in Italy [2,3] found that, in summertime, night-time dipping was less evident and SBPs were slightly increased; it was only with day-time BP measurements that the summertime decrease was evident. The night-time SBP increase was particularly apparent in elderly subjects receiving antihypertensive medication (type not specified).…”
Section: Night-time Dippingmentioning
confidence: 99%
“…The night-time SBP increase was particularly apparent in elderly subjects receiving antihypertensive medication (type not specified). While noting that "milder sleep problems associated with hot weather cannot be completely excluded" [3], and that there may be "different sleeping behaviors between summer and winter" [2], the authors suggested that there is often a, clinic-directed or self-directed, reduction in medication in summertime, either because of a measured daytime lowering of BP, or because it is "common knowledge" that such lowering would have occurred [2]. Thus, those who would reduce the number of medications, or reduce dosages (as in the present study), were cautioned by Modesti et al [3] that "the results of our study clearly indicate that the practice of reducing treatment in the summer in the elderly based on low clinic BP values is not good, because it might be responsible for a potentially dangerous increase in night BP."…”
Section: Night-time Dippingmentioning
confidence: 99%